Association of the geomagnetic and meteorological parameters in tropics - RAO, D. R. K.; SONTAKKE, K. G. (MAUSAM, 1982)
Using long series of the geomagnetic field observations at Alibag and corresponding formed from barometric pressure at Colaba (Bombay), biennial, pole-tide, annual and semi-annual signals are derived by cross spectral analysis technique, The possible solar-weather geomagnetic relations at these periodic variations are discussed. It is suggested that a study on the relative phase associations between the geomagnetic field and the pressure at annual and semi-annual cycles In time domain can be pursued towards the application aspect of the relationship.